2024
DOI: 10.1515/med-2024-0938
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sleep duration is associated with sarcopenia in older Chinese people: A large retrospective cross-sectional study

Xilin Peng,
Ruihao Zhou,
Congqi Liu
et al.

Abstract: Aim Abnormalities in sleep patterns are a common health problem for the older adults. The relationship between sarcopenia and sleep duration in older people is controversial. This research is to examine the association between sleep duration and sarcopenia. Methods We drew 21,095 adults from the China Health and Retirement Longitudinal Survey (CHARLS). Not only we explore the relationship between sleep duration and sarcopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…We found that the difficulty in falling asleep, the use of sleep drugs, and consulting a doctor for sleep problems were higher in females, in line with previous studies reporting differential sleep in females compared to males [ 37 ]. Moreover, recent research has shown a higher prevalence of sarcopenia in the short sleep and long sleep duration group compared with women in the normal sleep duration group, and these gender differences in sleep patterns are consistent with our findings [ 17 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that the difficulty in falling asleep, the use of sleep drugs, and consulting a doctor for sleep problems were higher in females, in line with previous studies reporting differential sleep in females compared to males [ 37 ]. Moreover, recent research has shown a higher prevalence of sarcopenia in the short sleep and long sleep duration group compared with women in the normal sleep duration group, and these gender differences in sleep patterns are consistent with our findings [ 17 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Long sleep showed more than twice the frequency in sarcopenic (22.67%) relative to nonsarcopenic (9.47%) participants, and 42.5% of the participants sleeping 9 or more hours developed sarcopenia. Similar results were found in older Chinese [23,30] and Korean [18] population cohorts, where long sleep would increase this risk twofold [19], using the same cut-off points [18,30].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation